The library of light and shadow : a novel - Rose, M. J., 1953- (The Daughters of La Lune, 2017)
"In this riveting and richly drawn novel from "one of the master storytellers of historical fiction" (New York Times bestselling author Beatriz Williams), a talented young artist flees New York for Paris after one of her scandalous drawings reveals a darksecret--and triggers a terrible tragedy. In the wake of a dark and brutal World War, the glitz and glamour of 1925 Manhattan shine like a beacon for the high society set, desperate to keep their gaze firmly fixed to the future. But Delphine Duplessi sees more than most. At a time in her career when she could easily be unknown and penniless, like so many of her classmates from L'École des Beaux Arts, in America she has gained notoriety for her stunning "shadow portraits" that frequently expose her subjects' most scandalous secrets. Most nights Delphine doesn't mind that her gift has become mere entertainment--a party trick--for the fashionable crowd. Then, on a snowy night in February, in a penthouse high above Fifth Avenue, Delphine's mystical talentleads to a tragedy between two brothers. Devastated and disconsolate, Delphine renounces her gift and returns to her old life in the south of France where Picasso, Matisse, and the Fitzgeralds are summering. There, Delphine is thrust into recapturing thepast. First by her charismatic twin brother and business manager Sebastian who attempts to cajole her back to work and into co-dependence, then by the world famous opera singer Emma Calve, who is obsessed with the writings of the fourteenth-century alchemist Nicolas Flamel. And finally by her ex-lover Mathieu, who is determined to lure her back into his arms, unaware of the danger that led Delphine to flee Paris for New York five years before. Trapped in an ancient chateau where hidden knowledge lurks in the shadows, Delphine questions everything and everyone she loves the most--her art, her magick, her family, and Mathieu--in an effort to accept them as the gifts they are. Only there can she shed her fear of loving and living with her eyes wide open"--